Code of Good Practices on Fiscal Transparency, revised April 2007. (Policy Papers; Policy Paper ;, 2007)
The IMF has revised its Code of Good Practices on Fiscal Transparency, following a public consultation process. Nine new practices have been added to the Code and many existing practices have been broadened in scope. The four pillars of the original Code remain unchanged: clarity of roles and responsibilities, open budget processes, public availability of information and assurances of integrity. The revised Code will be used in IMF surveillance and in voluntary assessments of fiscal transparency in member countries under the standards and codes initiative. Two associated documents - the Manual on Fiscal Transparency (2007) and the Guide on Resource Revenue Transparency (2007) - provide supporting in-depth coverage of good practices.